Cosmopolitanism in practice - Nowicka, Magdalena; Rovisco, Maria (Global connections (Ashgate (Firm)), 2009)
The volume provides empirical research to show how people actually embrace cosmopolitan ideas and attitudes. It studies 'cosmopolitanism in practice', looking at the social and institutional environments in which cosmopolitanism shapes everyday life experiences and identities. Contributors to the volume include Ulrich Bech, Stephen Vertovec, Rob Kroes and Natan Sznaider. Their research draws on a variety of intellectual disciplines, international contexts and methodological traditions from a range of local/global sites.